Speech Acts Found in English Tourism Slogans Used in Indonesia - Giyatmi, Giyatmi; Astuti, Purwani Indri; Wijayava, Ratih (State institute of islamic studies salatiga, 2021)
The research aims at describing the types and functions of speech acts in the tourism slogan in Indonesia. There has already been much research on tourism slogan, but only a few studies focusing on linguistics. To broaden the study of tourism slogans from a linguistics perspective, the research focuses on the speech acts in the tourism slogans. It belongs to descriptive qualitative research by focusing on the phenomena of tourism slogans in society. The data of the research are tourism slogans of some cities in Indonesia found on the internet. The technique of data collection used is content analysis. The technique of data analysis consists of data reduction, data display, and verification. There is no data reduction in this research. Data is displayed in the table and the last step data is analyzed based on the problem statements. The researchers found 31 data of tourism slogans. There are 4 types of speech acts in tourism slogans namely representative speech acts (13 data), directive speech acts (7 data), commissive speech acts (3 data), and expressive speech acts (8 data). The researchers find 3 functions of speech acts in the tourism slogan such as giving information about the history of the city, nickname of the city, hope or idea of the city (19 data), asking (7 data), and promising (5 data). The findings show that there is a tendency to be very simple in the slogans found. Besides, the slogans come with an exclusive appeal by emphasizing the effective component in the message.Keywords: tourism, slogans, speech acts.